Experience in Immunizing HIV-Infected Children against Pneumococcal Infection and Influenza - O. I. Nazarova; E. A. Alle; L. V. Puzyreva; L. N. Fursevich; T. V. Antipova (Эпидемиология и вакцинопрофилактика)
Relevance. The lethal outcomes of HIV infection are determined by secondary diseases, among which tuberculosis and pneumonia take the leading place. Vaccination is an important way to reduce and prevent the development of infectious diseases in both adults and children. Particular attention is paid to children with HIV infection, the incidence of which is much higher in comparison with children without HIV positive status. The purpose of the study was to study the effectiveness of the prevention of lower respiratory tract infections with pneumococcal and influenza vaccines in HIV-infected children. Materials & Methods. The material was data from medical records about HIV-infected children. The research method is visual using retrospective analysis. Results. Immunological indicators and the general health status of HIV-infected children were assessed during their registration with the regional AIDS center. Changes in the immunological status of patients under dynamic observation were described. The timing of vaccination was analyzed and a comparison was made with the development of bacterial diseases in HIV-infected children. Conclusions. A low incidence of bacterial infections and the absence of pneumococcal pneumonia in HIV-infected children were revealed. Vaccination against pneumococcal infection and influenza must be given to all HIV-infected children from the moment they are registered with a regional specialized medical institution.